Sustainable production of extracellular polymeric substances and iron or copper complex from glutinous rice processing wastewater - Chen, Zhen; Wang, Shilei; Hui, Zhichao; Wang, Fei; Ye, YuXin; He, Yi; Li, Yanqing; Yu, Zhidan; Cai, Yafan; Zhuang, Wei; Liu, Dong; Wang, Zhi; et al. (Frontiers in Sustainable Food Systems, 2024)
Essential trace minerals play vital roles in maintaining human and animal health. However, an overdose of the existing inorganic trace minerals is prone to induce detrimental effects that outweigh positive benefits. In this study, an extracellular polymeric substances (EPS)-producing bacterium, identified as Bacillus licheniformis CCTCC M2020298, was isolated from marine using glutinous rice processing wastewater as enrichment medium. The EPS yield of Bacillus licheniformis CCTCC M2020298 could reach 8.62 g/L by using glutinous rice-processing wastewater containing medium. Furthermore, the potential of the EPS as a carrier for synthesizing EPS-iron (Fe) and EPS-copper (Cu) complex was explored. The results showed that the optimum condition for the synthesis EPS-Fe were the reaction temperature 70°C, pH 8.5–9.0 and mass ratio of EPS to trisodium citrate 2:1. The iron content of EPS-Fe reached 77.4 mg/g. Under the same condition, the copper content of EPS-Cu reached 90.7 mg/g. The elemental composition, functional groups and valence state of the mineral elements of EPS-Fe and EPS-Cu were well characterized. The EPS-Fe and EPS-Cu exhibited antioxidant activity in scavenging ·OH, DPPH and ·O2− free radicals, thereby leading to reduced oxidative stress and apoptosis levels in human colonic epithelial cells in vitro. They also inhibited the proliferation of mouse hepatocellular carcinoma H22 and the growth of intestinal pathogens in vitro. This study provided an effective avenue for EPS production from glutinous rice processing wastewater and proved the potential of EPS-Fe and EPS-Cu complexes as a new-type comprehensive essential trace mineral supplement.